2017
DOI: 10.3389/fphar.2017.00261
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dendrimers on Solubility of Hydrophobic Drug Molecules

Abstract: Adequate aqueous solubility has been one of the desired properties while selecting drug molecules and other bio-actives for product development. Often solubility of a drug determines its pharmaceutical and therapeutic performance. Majority of newly synthesized drug molecules fail or are rejected during the early phases of drug discovery and development due to their limited solubility. Sufficient permeability, aqueous solubility and physicochemical stability of the drug are important for achieving adequate bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(86 citation statements)
references
References 165 publications
2
83
0
1
Order By: Relevance
“…Since then, it has been shown that G4-6 PAMAM dendrimers mimic the topology of micelles and their accessible interiors could be used to encapsulate small guest molecules, such as hydrophobic drugs [29]. The open, flexible structure of lower generation dendrimers (G0-3) and the rigid surface of high generation dendrimers due to steric branch crowding (G7-10) provided less efficient encapsulation [30].…”
Section: Cargo and Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, it has been shown that G4-6 PAMAM dendrimers mimic the topology of micelles and their accessible interiors could be used to encapsulate small guest molecules, such as hydrophobic drugs [29]. The open, flexible structure of lower generation dendrimers (G0-3) and the rigid surface of high generation dendrimers due to steric branch crowding (G7-10) provided less efficient encapsulation [30].…”
Section: Cargo and Drug Deliverymentioning
confidence: 99%
“…In addition to encapsulation in the dendrimer interior, the terminal functional groups at the dendrimer periphery can be used for complexation and conjugation of larger molecules. For instance, drug molecules and targeting moieties have been covalently attached to dendrimer surfaces [29]. The reactive amine groups on the PAMAM dendrimer periphery have also been functionalised with folates [33] and carbohydrates (coined glycodendrimers) [34] for cell specific targeting.…”
Section: Cargo and Drug Deliverymentioning
confidence: 99%
“…Many compounds that are excellent candidates as potent drugs against some pathologies do not continue with more advanced studies, due to their limited aqueous solubility. In recent years, several researches have been focused to solubilize powerful hydrophobic drugs to increase their bioavailability [76]. Some research has been conducted on the study of physicochemical parameters such as, water solubility, LogP, polar surface area, and the number of hydrogen bond acceptor and hydrogen bond donors as a measurement to elucidate the drug molecules solubility grade [77].…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…Conjugated drugs have a reduced metabolism and reduced renal clearance, which leads to an increase half‐life in the bloodstream . Nanocarriers can also improve the aqueous solubility of a hydrophobic drug, providing a higher bioactive drug concentration in the bloodstream . Interestingly, these PK improvements allow selective accumulation of nanocarriers in leaky hypervascularized tissues with poor lymphatic drainage such as tumors .…”
Section: Introductionmentioning
confidence: 99%